Let me finish! - d uthor; Roxas, Isabel (Los Angeles : Disney/Hyperion, 2016)
A young boy wants to read his favorite books without interruption, but the creatures around him keep spoiling the ending!
School Library Journal, June 2016
Horn Book, April 2017
Library Media Connection, October 2016
1.7
K-3
AD450L
Keywords: Books and reading -- Fiction; Animals -- Fiction; Humorous fiction